2022
DOI: 10.3390/app12126285
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Capillary Barrier on Water–Oil Movement in Water Flooding

Abstract: Water flooding technology is widely used to improve oil recovery efficiency in oilfields. The capillary barrier effect induced by the complex pore structures in the reservoir rocks is a crucial reason for the trapping of a great deal of residual oil in oil reservoirs after water flooding. However, the formation condition along with the effect on the recovery rate of the capillary barrier under different wettability conditions should be investigated further. To bridge the gap between the microscopic mechanism o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The specific values of the water-air factor are determined by various geological and field conditions for the implementation of the process. However, with an increase in oil density and viscosity (more precisely, with an increase in coke concentration), the required water-air factor decreases [98]. If the values of the water-air factor are less than those indicated, then the transfer of heat to the area ahead of the combustion front decreases.…”
Section: Wet In Situ Combustionmentioning
confidence: 97%
“…The specific values of the water-air factor are determined by various geological and field conditions for the implementation of the process. However, with an increase in oil density and viscosity (more precisely, with an increase in coke concentration), the required water-air factor decreases [98]. If the values of the water-air factor are less than those indicated, then the transfer of heat to the area ahead of the combustion front decreases.…”
Section: Wet In Situ Combustionmentioning
confidence: 97%
“…[4,5] A significant fraction of the remaining oil within the rock pores is microscopically trapped due to capillary barriers induced by the complex structure inside the pores of rocks. [6][7][8] By reducing the interfacial tension (IFT) between the displacing fluid and oil, the surfactant can facilitate mobilization of the oils trapped in the rock pores. [9][10][11] In addition, surfactants are capable of changing the wetting state of the rock surface from oil-wet toward a neutral-or water-wetting state so that attached oils on the rock surfaces can be released and moved toward the production well.…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies revealed that the pore structure and wettability of porous media play a pivotal role in controlling two-phase immiscible displacement patterns, residual oil formation, and the rate of oil recovery rate [7][8][9][10]. Further, the capillary barrier effect, resulting from the abrupt change in geometry between the minor and major empty regions of porous media, is the fundamental cause of residual oil formation [16][17][18][19][20]. Here, the capillary barrier effect is defined as a phenomenon where the invading fluid stops advancing until the waterflooding pressure exceeds a specific value to induce fluid motion.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the capillary barrier effect is defined as a phenomenon where the invading fluid stops advancing until the waterflooding pressure exceeds a specific value to induce fluid motion. However, current investigations [16][17][18] concerning the capillary barrier phenomenon are phenomenological, and an accurate and exhaustive characterization of the pore-level flow dynamics quantitatively within porous media is essential for mobilizing the trapped oil in pore spaces.…”
Section: Introductionmentioning
confidence: 99%